혀의 후방부에 발생한 연골성 분리종과 동반된 소타액선의 선종양성 과증식 - 박종찬; 김원기; 김한종; 이준; 윤정훈 (대한구강악안면병리학회지, 42(1), 2018)
“Cartilaginous choristoma” refers to as a tumorlike cartilaginous mass composed of normal tissues in an abnormal location. Oral cartilaginous choristomas are extremely rare. Although its rarity, most intraoral choristomas occur in the tongue. Adenomatoid hyperplasia of the minor salivary glands may be seen on the minor salivary gland bearing areas, especially seen on the palate. This report describes a case of firm mass on the left lateral tongue that was resulted cartilaginous choristoma associated with adenomatoid hyperplasia, which occurred in a 23-year-old male patient. And It hasn’t recurred during 17 months after complete excision. KCI Citation Count: 0